Increasing The TNF-α Levels In Nasal Lavage Liquid And Pulmonary Function Decrease Of Rice Mill Operator Exposed To Lipopolysaccharide (LPS) Endotoxin (International Journal of Scientific Research and Management (IJSRM), 2015)
Background: Exposure to endotoxin lipopolysaccharide in rice dust causes the inflammationinrespiratory tractwhich is characterized by an increase in Tumor Necrosis Factor Alpha (TNF-α) as well as the decline in pulmonary function of the rice mill operators. Objective: The aim of this study was to analyze the correlated of endotoxin LPS to increased levels of TNF-α in nasal lavage liquid and pulmonary function decline of the rice mill operators. Methods: This study was designed as a prospective longitudinal study.Dust sampling conducted during 8 hourswhile sampling the nasal lavage fluid and pulmonary function measurements made before and after the work (cross shift). Levels of TNF-α and endotoxin LPS subsequently analyzed using ELISA method, afterwards LPS analyzed by LAL method. Pulmonary function was analyzed by spirometry. Results: The mean levels of endotoxin LPS in the dust of ricewas 56.36±5.83 EU/m3. There are enhancement in the levels of TNF-α after the work (paired-samples t test:p=0.000) in which TNF-α levels increased in all rice mill operator after work. FVC decline of 72.73% and 63.64% for FEV1. Pulmonary function status after the work is: normal =36.36%, obstruction and restriction =36.36% =27.27%. Level of LPS endotoxin correlated to the increase in TNF-α in nasal lavage fluid workers (multiple linear regression test:p =0.000). Endotoxin LPS correlated tothe value ΔFVC and ΔFEV1 (multiple linear regression test:p